Companion dogs show signs of jealous behaviour toward non-living agents - Judit Abdai; Beatrix Laczi; Fabio F. Agostinho; Ádám Miklósi (Scientific Reports)
Abstract Dogs engage in social interactions with robots, yet whether they perceive them as social agents remains uncertain. In jealousy-evoking contexts, specific behaviours were observed exclusively when dogs’ owners interacted with social, rather than non-social rivals. Here, we investigated whether a robot elicits jealous behaviour in dogs based on its level of animateness. First, dogs observed a robot either moving mechanistically, or showing animate motions in a non-interactive, or interactive manner towards a human. Then, in consecutive trials the owner interacted with a rival dog, the robot, and read a magazine, while ignoring the subject. Dogs displayed more owner-oriented behaviours, interaction interruption, vocalization and snapping when the owner attended the rival dog compared to reading. Dogs showed intermediate interest toward the robot but snapped more toward the robot than the magazine. Thus, dogs adjust their jealous behaviour to the actual rival, and indirect, brief experience is sufficient to consider the robot as distinct from typical inanimate objects.